1997
DOI: 10.1046/j.1365-2826.1997.00661.x
|View full text |Cite
|
Sign up to set email alerts
|

Dehydroepiandrosterone 7α‐ and 7β‐Hydroxylation in Mouse Brain Microsomes. Effects of Cytochrome P450 Inhibitors and Structure‐Specific Inhibition by Steroid Hormones

Abstract: Presently, several works question the effects of dehydroepiandrosterone (DHEA) reported in vivo and designate its 7-hydroxylated metabolites as native antiglucocorticoids and potent mediators in the triggering of immune response. Among mouse tissues and organs, and second to liver, the largest production of 7alpha-and 7beta-hydroxylated derivatives of DHEA takes place in brain microsomes. To contribute to identification of cytochromes P450 (CYPs) responsible for 7alpha- and 7beta-hydroxy-DHEA production, effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
11
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 12 publications
4
11
0
Order By: Relevance
“…The verified occurrence of DHEA 7a-hydroxylase and DHEA 17-ketosteroid reductase activity in the human temporal lobe (Figs 2, 4 and 5) is in accordance with results obtained from rodent brain tissue experiments (Akwa et al 1992;Doostzadeh et al 1997;Rose et al 1997;Fig. 6).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The verified occurrence of DHEA 7a-hydroxylase and DHEA 17-ketosteroid reductase activity in the human temporal lobe (Figs 2, 4 and 5) is in accordance with results obtained from rodent brain tissue experiments (Akwa et al 1992;Doostzadeh et al 1997;Rose et al 1997;Fig. 6).…”
Section: Discussionsupporting
confidence: 89%
“…3b). The cytochrome P450 inhibitor ketoconazole was shown to be a potent inhibitor of microsomal mouse brain 7a-hydroxylase activity (Doostzadeh et al 1997). According to these findings, the present study revealed that ketoconazole is also a strong inhibitor of human brain tissue 7a-hydroxylase activity (Fig.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…In rodent brain, 7␣-hydroxylation is the major ex vivo metabolic route for DHEA, pregnenolone, and A/enediol (24,25,29,31,(33)(34)(35) and, in brain and other tissues, for oxysterols/bile acids (25-and 27-hydroxycholesterol, 3␤-hydroxy-5-cholestenoic acid, 3␤-hydroxy-5-cholenoic acid; Ref. 29), although 7␤-and 6␣-hydroxylation have also been recorded.…”
mentioning
confidence: 99%
“…7-hydroxylation in rat liver homogenate microsomes was characterized (Stárka and Kutová, 1962) and the 7-hydroxylation of dehydroepiandrosterone was discovered in various tissues, including of the brain (Akwa et al, 1992(Akwa et al, , 1993Doostzadeh and Morfin, 1996;Doostzadeh et al, 1997;Rose et al, 1997). Numerous authors paid attention to the presence and role of 7-oxygenated dehydroepiandrosterone derivatives in the brain (Morfin and Stárka, 2001).…”
mentioning
confidence: 99%